Parkinsonism following Bee Sting: A Case Report - Ruchika Mittal; Sanjay Munjal; Dheeraj Khurana; Ashok Gupta (Case Reports in Neurological Medicine)
We are reporting here a rare case of Parkinsonism (Hypokinetic dysarthria) caused after a bee stung, a member of the hymenoptera order. The main aim of this report is to orient the clinicians with the possibility of extrapyramidal syndromes because of hymenoptera stings.